2001
DOI: 10.1111/j.1749-6632.2001.tb03712.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sézary T Cell‐activating Factor, Chlamydia pneumoniae, and Cutaneous T Cell Lymphoma

Abstract: Séezary T cell‐activating factor (SAF) was originally defined as an inducer of functional interleukin‐2 (IL‐2) receptors on normal and malignant T cells in patients suffering from Sézary syndrome. In fact, a combination of SAF and IL‐2 stimulated the propagation of T cell lines from the peripheral blood mononuclear cells (PBMC) of those patients, with approximately one third of those cell lines containing the predominant malignant clone as determined via cytogenetic and/or T cell receptor gene rearrangement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 36 publications
(72 reference statements)
0
25
1
3
Order By: Relevance
“…A role in the pathogenesis of Sézary T-cell lymphoma has been proposed for skin-associated microbes such as Staphylococcus aureus 36 and Chlamydia. 37 Other studies reported an association between this lymphoma and cytomegalovirus 38 or Epstein-Barr virus infections. 39 In this context, microbial ODN-mediated cell triggering may induce uncontrolled proliferation of KIR3DL2 ϩ Sézary T cells, possibly representing an early event in the tumorigenic process leading to the malignant lymphoma.…”
Section: Discussionmentioning
confidence: 89%
“…A role in the pathogenesis of Sézary T-cell lymphoma has been proposed for skin-associated microbes such as Staphylococcus aureus 36 and Chlamydia. 37 Other studies reported an association between this lymphoma and cytomegalovirus 38 or Epstein-Barr virus infections. 39 In this context, microbial ODN-mediated cell triggering may induce uncontrolled proliferation of KIR3DL2 ϩ Sézary T cells, possibly representing an early event in the tumorigenic process leading to the malignant lymphoma.…”
Section: Discussionmentioning
confidence: 89%
“…Other associations between bacterial infection and B-cell proliferation have been examined in a few studies. Among these, H. pylori seropositivity in childbearing women has been linked with childhood acute lymphocytic leukemia in their offspring (147), and Chlamydia pneumonia has been associated with lung MALT lymphoma (44) and the Séz-ary syndrome (5). However, the lack of sufficient data precludes any conclusions about these associations at this time.…”
Section: Antigen-driven Lymphoproliferationmentioning
confidence: 86%
“…It has also been suggested that bacterial agents, such as Staphylococcus aureus (Tokura et al, 1992;Jackow et al, 1997) or Chlamydia pneumoniae (Abrams et al, 2001), might contribute to MF pathogenesis by acting as persistent antigens, thus exacerbating and/or perpetuating chronic T-cell expansion and cutaneous inflammation.…”
Section: Discussionmentioning
confidence: 99%